Ethnic and Religious Tolerance in Indonesia - Wijaksono, Agung (Universitas Airlangga, 2023)
This research focuses on the factors that influence tolerance in Indonesia. In this study, tolerance is seen from a person's attitude towards religious and ethnic differences. Data used are the results of Sosial Ekonomi Nasional Modul Sosial Budaya dan Pendidikan (Susenas MSBP) survey in 2021 conducted by Badan Pusat Statistik (BPS). This study uses ordinal logistic regression analysis and the results show that demographic factors (residence area and age) and socio-economic factors (education, poverty status, working status, and interaction with others) are the main factors that influence tolerance attitudes in Indonesia. individuals who live in urban areas, are highly educated, and interact with others, are more tolerant in accepting leaders, friends, and activities from different religions and ethnic groups. Older people have a higher tolerance attitude than younger people in accepting leaders of different religions and ethnicities. Poor households are more likely to accept leaders and friends of different religions and ethnicities, but less likely to accept leaders and activities of different ethnicities. The results also show that working individuals are less likely to accept activities from different religions/ethnic groups.